Finite element analysis of lumbosacral reconstruction after partial sacrectomy - Zheng, Longpo (International Scientific Literature, Inc., 2014)
BACKGROUND: The biomechanical property of MGT for patients who underwent partial sacrectomy is not well documented, so this study aimed to investigate biomechanical property of lumbosacral reconstruction after partial sacrectomy. MATERIAL/METHODS: Three 3-dimensional finite element models of lumbosacral region were established: 1) an intact model (INT), 2) a defective model in which partial sacrectomy was performed cephalad to S1 foramina (DEF), and 3) a reconstructed model (REC). RESULTS: Displacements of anchor point on L3 vertebrae in INT, DEF, and REC model were 6.63 mm, 10.62 mm, 4.29 mm (titanium), and 3.86mm (stainless steel), respectively. Stress distribution of the instrument in REC model showed excessive concentration on the caudal spinal rod, which may cause rod failure between spine and ilia. Maximum von Mise stress of the stainless steel instrument was higher than titanium instruments, and values of stress of the anchor point around the sacroiliac joint in the REC model were 26.4MPa with titanium instruments and 23.9 MPa with stainless steel instruments. CONCLUSIONS: Lumbosacral reconstruction can significantly increase stiffness of the spinopelvis of patients who underwent partial sacrectomy. However, the rod between L5 and ilia is the weakest region of all instruments. Stainless steel instruments have higher risk of rod failure and are less suitable for lumboiliac arthrodesis than titanium instruments.